PENGARUH FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL REPORTING - Noviani, Dian Septi; Zakaria, Adam; Nasution, Hafifah (LPPM Universitas Bina Bangsa, 2024)
This research was conducted with the aim of finding out the influence of external pressure, ineffective monitoring, change in auditor, change in directors, frequency of ceo’s picture on fraudulent financial reporting. This research uses companies in the infrastucture sector listed on the Indonesia Stock Exchange during the 2020-2022 period as the population. The research sample was selected using the purposive sampling method and produced 60 observation data. Data were analyzed using logistic regression analysis techniques and processed with the SPSS version 26 application. The research results show that External Pressure has a effect on fraudulent financial reporting, while ineffective monitoring, change in auditor, change in directors, frequency of ceo’s picture have no effect on fraudulent financial reporting